SELF-CONSOLIDATING CONCRETE USED IN THE MONOLITHIC CONSTRUCTION OF EARTHQUAKE-RESISTANT TALL BUILDING - S. A. Aliev; T. S. Murtazayeva; M. S. Saydumov; M. S. Salamanova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The development of high-strength concrete based on experience both with domestic and foreign concretes has led to the production of a self-consolidating concrete (SCC) formula. Method. Raw materials sourced from the Chechen Republic were used in the SUBconcrete formula, based on materials having different classes of compressive strength as well as the incorporation of polycarboxylate as an additive. Results. An investigation was carried out on natural and technogenic raw materials from the Chechen Republic and other regions of the country. Compositions of high-grade SCC with a compressive strength of B100 and higher are achieved with an integrated approach using both natural and man-made raw materials. The formulae of the basic concrete reinforcing technology are examined together with their physico-mechanical properties. The results of the study of locally sourced concrete, as well as that purchased from "Pavlovskgranit" and OOO "Progress" for testing from the Republic of North Ossetia–Alania, are provided. Of the various manufacturers' cements investigated, the highest quality Portland cement CEM I 4.5N was selected from the Tula cement manufacturers in the town of Chiri-Yurt. The fillers used were microsilica sourced from the Novokuznetsk plant, inactivated MP-1 mineral powder produced in Kaluga and fly ash sourced from Nevinnomyssk. Conclusion. The results of the studies show that the raw material potential of our country allows for the production of self-consolidating concrete from class B 25 to B100 and higher for use in monolithic construction, including high-rise. The concrete compositions arrived at are characterised by their high physical and mechanical properties and can be used in high-rise concrete construction sites operating in earthquake-prone areas.